Older Adults Perception with respect to M-Health applications: a systematic review - Benavides-Guerrero, Carolina (Universidad de Sonora, 2022)
Introduction: M-Health refers to the use of mobile devices for health care. There are several apps dedicated to health, especially for older adults; however, it is essential to identify their perception when considering the skills of the elderly for the management and use of apps and mobile devices. Objective: To know the perception of the elderly regarding M-Health apps. Methodology: A systematic review in the following databases: PubMed, Journal of Medical Internet Research, Web of Science and Wiley Online Library. Articles in the English language, published between 2013 and 2021 were included. Inclusion criteria: Elderly people using mobile devices were included in the sample. Perception about m-health apps was reported. The guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses were followed. A total of 569 articles were found, of which a sample of 20 articles was obtained after the review. Results: The use of various mobile devices, apps and websites was found. The perception referred by the older adults was positive because they were useful, comfortable, easy to use; although they also expressed negative perception due to fear of using them, not knowing how to use them, lack of security of personal data and costs. Conclusion: The perception about m-health is that these apps have more positive than negative aspects; the negative perceptions were generated by the difficulty and fear felt by elderly adults to make use of M-Health applications.